(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
The study explores the transformation of medieval Bengal with the arrival of Muslims, marking the dawn of a Golden Age. Bengali Muslims, now the second-largest Muslim ethnic group globally, integrated into the region’s social fabric through immigration starting from the 8th century, accelerating after 1204. Immigrant Muslims and Muslim rulers, after 1204, connected Bengal with the benefits of the Islamic Golden Age of the medieval period. These immigrants, driven by religious, political, and economic motivations, established a substantial Muslim community and introduced Islamic principles that reshaped governance, justice, education, socio-economic conditions, trade, literature, and architecture in Bengal. The peaceful coexistence of immigrant Muslims, converted Muslims, and local Bengalis under Muslim rule fostered a multiethnic society enriched by Islamic cultural elements. The research delves into the gradual Islamization process in Bengal, characterized by the integration of Islamic customs and values into the existing social fabric. In addition, it examines the existing socio-economic condition of Bengal before the establishment of Muslim rule in Bengal. It also highlights the pivotal role of mosques and educational institutions in promoting Islamic teachings and fostering cultural exchanges. By analyzing primary and secondary sources, the study aims to provide a nuanced understanding of Bengal’s evolution during this period, emphasizing the motivations behind Muslim territorial control and the defining characteristics of the era. Despite the scarcity of precise historical records, the findings contribute to the broader scholarship on Bengal’s history, illustrating how the integration of Islamic elements led to a period of prosperity and cultural richness in medieval Bengal. JASBH, Vol. 69(2), 2024, pp. 175-201